“How To”: Write an Evaluation Terms of Reference (ToR) - Kwiringira, Japheth (Evaluation Capacity Development, 2014)
This resource provides the general principles of what a ‘Terms of Reference’ (ToR) is; how it is conceptualized, developed, and used to guide an evaluation. The document provides information regarding the expected content of the ToR (depending on the phase of the project cycle). This recommended method of writing a ToR is not prescriptive; the document is aimed at assisting those charged with the task of drafting a ToR1 for evaluating any kind of project. Drafting a ToR may be considered as a skill that tends to improve as more practical experience is gained
Keywords: Terms of Reference